Molecular-level insight into hot-melt loading and drug release from mesoporous silica carriers - Lizoňová, D; Mužík, J; Šoltys, M; Beránek, J; Kazarian, S G; Štěpánek, F (European journal of pharmaceutics and biopharmaceutics, 2018)
Drug amorphisation by loading to inorganic mesoporous carriers represents an emerging area of improving the dissolution rate and bioavailability of poorly water-soluble active pharmaceutical ingredients (APIs). In this work, for the first time, a molecular-level insight into the process of API loading to mesoporous SiO2 (silica) carriers by the hot-melt impregnation method and its subsequent release during dissolution was obtained using ATR-FTIR spectroscopic imaging. A physical mixture of ibuprofen crystals and mesoporous silica particles was heated and the dynamics of melt loading into the silica pore structure was directly observed in situ by ATR-FTIR spectroscopic imaging. The loss of crystallinity, the redistribution of the API in the silica pore network and the subsequent stabilisation of the amorphous form upon cooling were proven. The API was involved in two different kinds of molecular-level interactions: API dimers in the amorphous bulk, and individual API molecules adsorbed on the silica surface. The melt-loaded silica carriers were comprehensively characterised by DSC, SEM and dissolution tests, which proved dissolution rate enhancement due to amorphisation of the API. Drug release form the hot-melt loaded mesoporous silica carriers was observed in real time and the conditions leading to local re-crystallisation of super-saturated solution of the API were identified.
Keywords: Spectroscopy, Fourier Transform Infrared; adsorpce; oxid křemičitý; Water; voda; Silicon Dioxide; poréznost; Chemistry, Pharmaceutical; rozpustnost; uvolňování léčiv; Biological Availability; Ibuprofen; diferenciální skenovací kalorimetrie; vysoká teplota; Solubility; Drug Liberation; Crystallization; krystalizace; Adsorption; Calorimetry, Differential Scanning; ibuprofen; Hot Temperature; farmaceutická chemie; spektroskopie infračervená s Fourierovou transformací; Drug Carriers; Microscopy, Electron, Scanning; nosiče léků; biologická dostupnost; mikroskopie elektronová rastrovací; Porosity